Estimated mink home ranges using various home‐range estimators - Richard S. Halbrook; Marty Petach (Wildlife Society Bulletin)
ABSTRACT Although the American mink (Neovison vison) is a fairly common and valued semiaquatic furbearing species, studies evaluating space use by mink in North America are scarce. We implanted radiotransmitters in 8 male and 6 female mink living within 3 km of the Hudson River between Hudson Falls and Northumberland Dam, New York, USA, during 2009–2011 and estimated Minimum Convex Polygon (MCP), Minimum Bounding Circle (MBC), and Kernel Density Estimate (KDE) home ranges. We also estimated an Ecological Home Range (EHR) using habitat characteristics known to be important to mink. The MBC, MCP, and 95% KDE estimation methods produced home ranges that appear to include area not actually used by mink, while the EHR method appeared to more accurately reflect space used at a finer scale. The mean 95% KDE home‐range estimate was 2.3 times greater than the mean MCP estimated home range and 3.3 times greater than the mean EHR estimate. The size of individual mink EHRs ranged from 23 to 164 ha and did not differ between male and female. Our results indicate that mink home ranges can be quite variable and demonstrates the importance of selecting an estimation method based on management objectives. Home‐range curves and asymptotes calculated using the Michaelis–Menten equation are provided; Site Fidelity and Time To Statistical Independence calculations reported in the rhr package of the Program R Statistical software are discussed. © 2018 The Wildlife Society.